2017
DOI: 10.1128/mbio.00494-17
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis PhoY Proteins Promote Persister Formation by Mediating Pst/SenX3-RegX3 Phosphate Sensing

Abstract: The Mycobacterium tuberculosis phosphate-specific transport (Pst) system controls gene expression in response to phosphate availability by inhibiting the activation of the SenX3-RegX3 two-component system under phosphate-rich conditions, but the mechanism of communication between these systems is unknown. In Escherichia coli, inhibition of the two-component system PhoR-PhoB under phosphate-rich conditions requires both the Pst system and PhoU, a putative adaptor protein. E. coli PhoU is also involved in the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 41 publications
5
75
0
Order By: Relevance
“…Multiple genes of diverse functional categories (like mma4 , Rv2224c, ponA2 , and pstC2A1 ) identified in our Tn-seq screen have also been implicated in maintaining intrinsic tolerance to a panel of stressors and antibiotics, including but not limited to acidic pH, lysozyme, SDS, isoniazid and rifampicin (31, 40, 41). A reasonable interpretation of this observation is that the restrictive conditions formed in biofilms may favor the growth of cells that are tolerant to both endogenous and exogenous stresses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple genes of diverse functional categories (like mma4 , Rv2224c, ponA2 , and pstC2A1 ) identified in our Tn-seq screen have also been implicated in maintaining intrinsic tolerance to a panel of stressors and antibiotics, including but not limited to acidic pH, lysozyme, SDS, isoniazid and rifampicin (31, 40, 41). A reasonable interpretation of this observation is that the restrictive conditions formed in biofilms may favor the growth of cells that are tolerant to both endogenous and exogenous stresses.…”
Section: Resultsmentioning
confidence: 99%
“…A corollary to this hypothesis is that monoculture biofilms of mutant cells that are intrinsically sensitive to antibiotics harbor fewer persisters than wild-type. To test this, we exploited the Δ pstC2A1 strain, which exhibits hypersensitivity to rifampicin (RIF) (40). Moreover, the mutant forms biofilms indistinguishable from wild-type, thereby allowing a direct assessment of the effect of intrinsic property of the cells without any compounding effect from an altered architecture, which is generally observed with other antibiotic sensitive mutants identified in this study (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that some other mechanisms may also be involved in PBST‐induced INH tolerance. Besides polyP, several other proteins and molecules have been shown to be involved in stress responses and generating drug‐tolerant cells (Dahl et al ., ; Chionh et al ., ; Namugenyi et al ., ). The expression level of katG is known to be negatively correlated with INH‐tolerance in mycobacterial cells (Wakamoto et al ., ); and our study showed that the expression of katG was repressed during PBST treatment (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 56%
“…Consistent with a need to balance poly-P production and metabolism for wild type fitness in C. jejuni others, have demonstrated that phoX and ppk1/ppk2 mutants also have survival defects in nutrient limiting condition (18). Increased poly-P was also observed in phosphate transport mutants of M. tuberculosis (32).…”
Section: Discussionmentioning
confidence: 95%